Evaluation of Power Quality in Off-Grid Power System - Stanislav Misak; Lukas Prokop; Petr Bilik; Petr Krejci (Communications - Scientific letters of the University of Zilina, 2015)
The energy independence, reliability and safety of energy distribution system operation as well as use of renewable resources have been hot research topics in recent years. This research leads to the development of active distribution grids with specific requirements. The Power Quality problems can arise when using renewable sources in active distribution grids. Problems are caused by decreased short-circuit power of local renewable sources, stochastic supply of electric energy from renewable sources and operating the active distribution grid in off-grid regime without connection to the external distribution system. In case of these conditions, the mutual interference between sources and loads is relevant and parameters of quality of electric energy can be exceeded. The results from analysis of quality of electric energy in the particular active distribution grid (off-grid power system) are introduced in this paper.